Kajian Molekular Tarsius sp. Pada Gen Penyandi Cytochrome Oxidase Sub-unit 2 Mitokondria - Widayanti, Rini; Handayani, Niken Satuti; Budiarsa, I. Made (Universitas Atma Jaya Yogyakarta, 2010)
Tarsius is an endemic species in Indonesia that is endangered. In-situ and ex-situ conservation of this species would yield better results if this genetic make up and diversity is determined. The objective of this ressearch was to study the specific genetic marker on COX2 gene of Tarsius sp. Sequencing of PCR product using primer COX2F and COX2R resulted in base sequence of 513 nts. Results of COX2 fragments sequencing were put on multiple alignment with other primates from Genbank with aid of software Clustal W, and were analyzed using MEGA program version 4.1. Eight different amino acid sites were found (amino acid no. 5, 6, 13, 14, 30, 35, 44 and 168). The genetic distance based on nucleotide COX2 calculated using Kimura 2-parameter model indicated that in the smallest genetic distance 0%, biggest 6.8% and average 2.3%. The phylogenetic tree using neighbor joining method based on the sequence of nucleotide and amino acid COX2 reveded differentiation among Tarsius from Lampung and Tarsius from Sulawesi, but could not be used to differentiate among T. dianae (from Central Sulawesi) and T. spectrum (from North Sulawesi).